2016
DOI: 10.1016/j.jmii.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Time to positivity in blood cultures of adults with nontyphoidal Salmonella bacteremia

Abstract: The TTP of blood cultures, interpreted with a cut-off point of <10 hours, in patients with NTS bacteremia may provide useful diagnostic and prognostic information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
3
7
1
Order By: Relevance
“…Although blood culture was negative for Salmonella sp. in our case, positive blood culture results have been reported in up to 30% of patients with Salmonella osteomyelitis [8].…”
Section: Discussionsupporting
confidence: 56%
“…Although blood culture was negative for Salmonella sp. in our case, positive blood culture results have been reported in up to 30% of patients with Salmonella osteomyelitis [8].…”
Section: Discussionsupporting
confidence: 56%
“…When screening the citations of the 80 studies, we identified an additional four studies that met our inclusion criteria, yielding a total of 84 eligible studies for analysis ( figure 1 ). 6 , 15 , 16 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ,…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, anaemia might be over-reported as a complication of non-typhoidal salmonella invasive disease in our study, since we were unable to ascertain whether it was present before the onset of non-typhoidal salmonella invasive disease. As a result, it was difficult to be confident that author-reported complications met the widely accepted definitions of clinical conditions, and to ascertain whether some clinical observations were actual Taoyuan, Taiwan, 1990 68 Kaohsiung, Taiwan, 2002 62 Taoyuan, Taiwan, 2003 104 Taipei, Taiwan, 2003 111 Taipei, Taiwan, 2004 60 Taipei, Taiwan, 2004 110 Tainan, Taiwan, 2005 43 Taipei, Taiwan, 2006 63 Taipei, Taiwan, 2006 112 Tainan, Taiwan, 2009 72 New Taipei City, Taiwan, 2012 73 Taipei and New Taipei City, Taiwan, 2014 45 Taipei, Taiwan, 2015 44…”
Section: Western Africamentioning
confidence: 99%
“…The TTP may depend on multiple factors, including the volume of blood inoculated, the time elapse from specimen collection to incubation, and the concentration of organism within the blood [1,3,7]. In our study, we demonstrated that factors associated with TTP <24 hours were an underlying disease of malignancy, endocarditis and vascular infection, thrombocytopenia, and clinical of SIRS.…”
Section: Discussionmentioning
confidence: 58%
“…A study among patients with E. coli bacteremia also reported that rapid TTP (<7 hours) was noted in patients who had active malignancies and neutropenia [1]. In addition, a study among patients with nontyphoidal salmonella bacteremia, rapid TTP (<10 hours) was associated with endovascular lesion and higher bacteremia score [3]. However, a study among children with S. pneumoniae bacteremia, no clinical or laboratory parameters was associated with the early growth of organisms [23].…”
Section: Discussionmentioning
confidence: 99%